Chemokines and Growth Factors Produced by Lymphocytes in the Incompetent Great Saphenous Vein - Ewa Grudzińska; Sławomir Grzegorczyn; Zenon P. Czuba (Mediators of Inflammation)
The role of cytokines in the pathogenesis of chronic venous disease (CVD) remains obscure. It has been postulated that oscillatory flow present in incompetent veins causes proinflammatory changes. Our earlier study confirmed this hypothesis. This study is aimed at assessing chemokines and growth factors (GFs) released by lymphocytes in patients with great saphenous vein (GSV) incompetence. In 34 patients exhibiting reflux in GSV, blood was derived from the cubital vein and from the incompetent saphenofemoral junction. In 12 healthy controls, blood was derived from the cubital vein. Lymphocyte culture with and without stimulation by phytohemagglutinin (PHA) was performed. Eotaxin, interleukin 8 (IL-8), macrophage inflammatory protein 1 A and 1B (MIP-1A and MIP-1B), interferon gamma-induced protein (IP-10), monocyte chemoattractant protein-1 (MCP-1), interleukin 5 (IL-5), fibroblast growth factor (FGF), granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), platelet-derived growth factor-BB (PDGF-BB), and vascular endothelial growth factor (VEGF) were assessed in culture supernatants by a Bio-Plex assay. Higher concentrations of eotaxin and G-CSF were revealed in the incompetent GSV, compared with the concentrations in the patients’ upper limbs. The concentrations of MIP-1A and MIP-1B were higher in the CVD group while the concentration of VEGF was lower. In the stimulated cultures, the concentration of G-CSF proved higher in the incompetent GSV, as compared with the patients’ upper limbs. Between the groups, the concentration of eotaxin was higher in the CVD group, while the IL-5 and MCP-1 concentrations were lower. IL-8, IP-10, FGF, GM-CSF, and PDGF-BB did not reveal any significant differences in concentrations between the samples. These observations suggest that the concentrations of chemokines and GFs are different in the blood of CVD patients. The oscillatory flow present in incompetent veins may play a role in these changes. However, the role of cytokines in CVD requires further study.